The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/mjt.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Administration Does Not Influence the Prognosis of Acute Myocardial Infarction: A Meta-Analysis

Abstract: In this meta-analysis, we found that the evidence on the safety and efficacy of oxygen was not only weak and inconsistent but also had modest statistical power. The variation in results was mainly because of the presence or absence of revascularization of the culprit artery. Adequately powered studies are needed to further delineate the role of oxygen in patients undergoing coronary revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our findings were consistent with the results of studies that evaluated the impacts of supplemental oxygen therapy in other clinical settings. Several RCTs and meta-analyses have demonstrated that oxygen therapy does not significantly reduce all-cause mortality, and can even increase the incidence of early myocardial injury and infarct size among AMI patients with normoxemia [8,[10][11][12][13][29][30][31][32][33]. A total of 11 RCTs including 6366 patients with acute stroke showed a nonsignificant increase in mortality at 3, 6, and 12 months in patients who received normobaric oxygen compared with those who received ambient air [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with the results of studies that evaluated the impacts of supplemental oxygen therapy in other clinical settings. Several RCTs and meta-analyses have demonstrated that oxygen therapy does not significantly reduce all-cause mortality, and can even increase the incidence of early myocardial injury and infarct size among AMI patients with normoxemia [8,[10][11][12][13][29][30][31][32][33]. A total of 11 RCTs including 6366 patients with acute stroke showed a nonsignificant increase in mortality at 3, 6, and 12 months in patients who received normobaric oxygen compared with those who received ambient air [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs and meta-analyses have demonstrated that oxygen therapy does not signi cantly reduce all-cause mortality, and can even increase the incidence of early myocardial injury and infarct size among AMI patients with normoxemia (8,(10)(11)(12)(13)(29)(30)(31)(32)(33). A total of eleven RCTs including 6,366 patients with acute stroke showed a nonsigni cant increase in mortality at three, six, and twelve months in patients who received normobaric oxygen compared with those who received ambient air (34). In addition, it was standard to perform neonatal resuscitation with 100% oxygen until multiple RCTs demonstrated that room air resulted in a lower incidence of infant mortality and hypoxic ischemic encephalopathy than 100% oxygen, thereby contributing to a dramatic change in guidelines and practice (35).…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings were consistent with the results of studies that evaluated the impacts of supplemental oxygen therapy in other clinical settings. Several RCTs and meta-analyses have demonstrated that oxygen therapy does not signi cantly reduce all-cause mortality, and can even increase the incidence of early myocardial injury and infarct size among AMI patients with normoxemia (8,(10)(11)(12)(13)(29)(30)(31)(32)(33). A total of eleven RCTs including 6,366 patients with acute stroke showed a nonsigni cant increase in mortality at three, six, and twelve months in patients who received normobaric oxygen compared with those who received ambient air (34).…”
Section: Discussionmentioning
confidence: 99%